2014
DOI: 10.1111/idj.12114
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of dental caries in children in the United Arab Emirates

Abstract: Dental caries has a significant impact on the general health and development of children. Understanding caries epidemiology is an essential task for the United Arab Emirates (UAE) policymakers to evaluate preventive programmes and to improve oral health. The purpose of this review is to collect and summarise all data available in the published literature on the epidemiology of dental caries in the UAE in children aged under 13 years. This will provide dental health planners with a comprehensive data summary, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 21 publications
2
17
0
1
Order By: Relevance
“…Saudi Arabia has a young population with persons under the age of 18 years accounting for nearly 40% of the population. The relationship between dental caries in childhood and caries experience as adults is a well-established one (5, 6). Numerous studies from across the region have confirmed the absence of proper oral hygiene and high caries rates in the samples of children studied (711).…”
Section: Introductionmentioning
confidence: 99%
“…Saudi Arabia has a young population with persons under the age of 18 years accounting for nearly 40% of the population. The relationship between dental caries in childhood and caries experience as adults is a well-established one (5, 6). Numerous studies from across the region have confirmed the absence of proper oral hygiene and high caries rates in the samples of children studied (711).…”
Section: Introductionmentioning
confidence: 99%
“…Dental caries is a very common chronic disease of childhood in both developed and developing countries. The term ‘early childhood caries’ (ECC) was adopted by the American Academy of Pediatric Dentistry (AAPD) in 1994 to replace the older term ‘Nursing Bottle Caries’.…”
Section: Introductionmentioning
confidence: 99%
“…8 In the UK, some had gone so far as to describe it as the "Gold Standard" for restoring the multi-surface carious molar. 9 Our study investigated the knowledge and practice of the HT. It showed that a majority of those surveyed had heard of (n=91, 60.6%) but not practiced (n=122, 81.4%) the HT.…”
Section: Discussion Of the Hall Technique (Ht)mentioning
confidence: 99%